Cold Protection of Foliage Plants in Shadehouses and Greenhouses - Robert H. Stamps; Seenivasan Natarajan; Lawrence R. Parsons; Jianjun Chen (EDIS)
ENH1168, a 10-page illustrated fact sheet by Robert H. Stamps, Jianjun Chen, Seenivasan Natarajan, and Lawrence R. Parsons, informs ornamental foliage plant growers about various cold protection measures that can be adopted before and during cold events to avoid or minimize losses due to chilling or cold injury. Includes glossary and references. Published by the UF Department of Environmental Horticulture, July 2010.